Modeling of electromagnetic separation of nonmetallic inclusions from magnesium melts - M Reza Afshar (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
In this work a mathematical model was developed to study the effect of electromagnetic force on the magnesium melt containing nonmetallic inclusion in an electrical isolated channel. The electromagnetic force exerted on the inclusion induced by DC current field was calculated. A three dimensional turbulent flow equations were solved numerically to compute the velocity field within the channel. On the basis of computed velocity and magnetic fields, the trajectories of inclusions were calculated using the equations of motion for inclusions. Parametric studies were carried out to evaluate the effect of various parameters such as current density, channel diameter and particle density on the removal efficiency of inclusions from magnesium melts.